Association between Electronic Cigarette Use and Asthma among High School Students in South Korea. - Jun Ho Cho; Samuel Y Paik (PLoS ONE)
Objectives Little is known about health outcomes related to electronic cigarette (EC) use, despite its growing popularity. The aim of this study is to investigate the association between EC use and asthma. Methods The study design is a cross-sectional study. A total of 35,904 high school students were included as the final study population. The presence of asthma was based on a student's self-reported doctor diagnosis of asthma in the past 12 months. Results Prevalence rates of asthmatics in 'current EC users' (n = 2,513), 'former EC users' (n = 2,078), and 'never EC users' (n = 31,313), were 3.9% (n = 98), 2.2% (n = 46) and 1.7% (n = 530), respectively. Comparing 'current EC' users with 'never EC' users, the unadjusted OR for asthma was 2.36 (95% CI: 1.89-2.94). In order to control for the effect of conventional cigarette (CC) smoking, after stratifying the subjects by the three CC smoking categories (never CC, former CC, and current CC), within the 'never CC' category, the unadjusted OR for asthma for 'current EC' users was 3.41 (95% CI: 1.79-6.49), and the adjusted OR was 2.74 (95% CI: 1.30-5.78). Severe asthma was reflected by the number of days absent from school due to asthma symptoms; current EC users had the highest adjusted OR for severe asthma compared to 'never EC' users. Conclusions When compared to a reference population of high school students in South Korea, EC users have an increased association with asthma and are more likely to have had days absent from school due to severe asthma symptoms. In conclusion, the results indicate that EC use may be a risk factor for asthma. The results may be useful in developing a scientific basis for the evaluation of a potential health hazard by EC.